Moving Beyond Uber - Stefan Kirchner; Nele Dittmar; Emilia Sophie Ziegler (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2022)
Discussions on organizational models and work in the platform economy often center on Uber as a~prominent example of a~digital marketplace that relies on venture capital and gig labor from self-employed drivers. This focus on Uber underestimates the diversity of organizational models and work types that likely arise from struggles between firms seeking to dominate emerging fields. Our exploratory results coming out of the field of "shared mobility" in Germany show that the platform economy harbors two modes: a~few digital marketplaces with gig labor and many app-enabled firms that build on smartphones to operate their mobility services with employees that perform app-enabled labor . In addition, some firms that rely on venture capital face several firms financed by incumbents from adjacent fields—in particular, car manufacturing. Overall, we find an absorption of platform technology by incumbents alongside disruption induced by start-ups. We conclude that German shared mobility comprises a~diversity of organizational models and work types beyond the Uber model, the mapping of which helps toward a~better understanding of the platform economy.
Keywords: 300; Mobility services; Organizational models; Markets as fields; Labor and working conditions; Platform capitalism; Mobilität Dienstleistung; Organisationale Modelle; Märkte als Felder; Arbeits- und Beschäftigungsbedingungen; Plattformkapitalismus